If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-5(x-6)=-2(10-x)-10
We move all terms to the left:
3x-5(x-6)-(-2(10-x)-10)=0
We add all the numbers together, and all the variables
3x-5(x-6)-(-2(-1x+10)-10)=0
We multiply parentheses
3x-5x-(-2(-1x+10)-10)+30=0
We calculate terms in parentheses: -(-2(-1x+10)-10), so:We add all the numbers together, and all the variables
-2(-1x+10)-10
We multiply parentheses
2x-20-10
We add all the numbers together, and all the variables
2x-30
Back to the equation:
-(2x-30)
-2x-(2x-30)+30=0
We get rid of parentheses
-2x-2x+30+30=0
We add all the numbers together, and all the variables
-4x+60=0
We move all terms containing x to the left, all other terms to the right
-4x=-60
x=-60/-4
x=+15
| 2x+.5x=180 | | x-0.2x=4520 | | 3+20x=19x+9 | | (8x+7)(x-3)=0 | | -2-r/3=5 | | X+11=4x= | | 150-100+43650=45675-175m | | 5h=4=7h=24 | | 5t-22=33 | | 15x–7=8x+2 | | g(25)=24(-14-39) | | 3x+15=-32 | | -x8=96 | | 2i-16=12(i+8) | | t+19=20 | | 7x^2-242x+663=0 | | 12x-9=8x+2 | | 24=(x-39) | | 0.15+0.05(10-x)=0.10(10) | | 2-3s=-7.72 | | x=310 | | 3.7+2h=5.7 | | 3x-5(x-2)=-4+3-1 | | h/7-17=-11 | | -3v=-8-7v | | 30+0.50c=1.25c | | 7=-0.4+2.3x | | h/16=1 | | h4+10=14 | | −36=-12y=48 | | 4=f-14 | | +=117284d |